Comparison of joint kinematics between different resisted sprint loads with different phases of acceleration of normal sprints in experienced sprinters - van den Tillaar, R. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to compare joint kinematics of different active resisted loads upon different phases of the acceleration (similar velocity) of a normal sprint. Fifteen experienced male sprinters performed a 50-m sprint with maximal effort from a start block, followed by a 10, 20, 30m with resisted sprints provided by a robotic pully system that gave resp. 65, 50, 25 and 10% reduction of peak velocity, while joint kinematics were measured. The main findings were that in the contact phase most kinematics were similar between the two. During the flight phase maximal hip and knee flexion and velocity were significantly higher in the resisted sprints compared with normal sprint, especially with high resisted loads. It was concluded that most joint kinematics of different active resisted loads are comparable with the different phases of the acceleration of a normal sprint.